Positive electrode active material for all-solid-state battery, method for preparing same, and all-solid-state battery comprising same
By introducing lithium-ion conductive oxide coating into the positive electrode active material of all solid state battery and adjusting relevant parameters, the problem of decreasing high output down-discharge capacity is solved, and the high capacity and long life characteristics of the battery are achieved.
Patent Information
- Application Number
- CN202380086340.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-12-16
- Filing Date
- 2023-11-08
- Publication Date
- 2025-08-01
AI Technical Summary
The discharge capacity of the existing lithium secondary batteries has dropped significantly under high output, and there is room for improvement in the initial capacity and charge and discharge life characteristics of the conventional positive electrode active materials coated with lithium ion conductive oxides.
A full-solid-state battery positive electrode active material containing a layered lithium transition metal oxide core and a lithium ion conductive oxide coating was used to form a coating to suppress the generation of a high-impedance layer by adjusting the peak intensity ratio I(003)/I(104), lithium/transition metal molar ratio (Li/Me), average grain size and specific surface area during X-ray diffraction spectroscopy.
The discharge capacity and life characteristics of the battery are improved at high output, the initial capacity and charge and discharge efficiency of the battery are improved, the contact interface between the active material and the solid electrolyte is enhanced, and the lithium migration path is stabilized.
Smart Images

Figure CN120418980A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a positive electrode active material for an all-solid-state battery, a method for preparing the same, and an all-solid-state battery including the same. More specifically, the present invention relates to a layered all-solid-state battery positive electrode active material, a method for preparing the same, and an all-solid-state battery including the same. Background Art
[0002] Recently, in the lithium secondary battery market, the requirements for increasing the driving range and improving the safety of electric vehicles have been continuously increasing. Therefore, it has become very important to develop lithium secondary batteries that have both excellent safety and high weight and volume energy densities. In particular, the energy capacity applied to electric vehicles reaches the level of dozens of kilowatt-hours, and there is a possibility of large-scale fires and explosions when the battery is damaged. Therefore, researchers are actively conducting research on replacing liquid electrolytes with solid electrolytes.
[0003] In particular, for the convenience of manufacturing, all-solid-state batteries mainly adopt a structure in which a solid electrolyte is applied inside the positive electrode as a secondary electrolyte for forming a lithium ion conduction path. For sulfide-based solid electrolytes, since they have high ionic conductivity and are easily deformed under pressure, high density can be achieved, and thus a large amount of research has been conducted.
[0004] For the positive electrode active material used in combination with the sulfide-based solid electrolyte in the positive electrode, similar to lithium ion batteries, recently, oxide-based positive electrode active materials having a layered structure of the NCM type or the NCA type have been mainly used. However, these positive electrode active materials react at the interface with the sulfide-based solid electrolyte to form a high-impedance layer. Therefore, in order to prevent such reactions from occurring on the surface of the active material, research on coating with a lithium ion conductive oxide to improve performance has been continuously carried out.
[0005] However, compared with the uncoated case, the conventional positive electrode active material coated with a lithium ion conductive oxide has been considerably improved in terms of the initial capacity and efficiency of the battery and the charge-discharge life characteristics. However, when the electrode active material loading is increased or at a high c-rate, there is a problem of a significant decrease in the discharge capacity. Summary of the Invention
[0006] Technical Problem to be Solved
[0007] Therefore, an aspect of the present invention aims to provide a positive electrode active material for an all-solid-state battery coated with a lithium ion conductive oxide, a method for preparing the same, and an all-solid-state battery including the same, which can improve the discharge capacity of the battery at a high c-rate and have excellent capacity and life characteristics.
[0008] Technical Solution
[0009] One embodiment of the present invention provides an all-solid-state battery positive electrode active material, comprising: a core comprising a layered lithium transition metal oxide; and a coating layer disposed on the core and containing a lithium ion conductive oxide, wherein the ratio of the diffraction peak intensity of the (104) plane to the diffraction peak intensity of the (003) plane, I(003) / I(104), is 1.20 to 1.40 when analyzed by X-ray diffraction spectroscopy, and the lithium / transition metal (Li / Me) molar ratio of the lithium transition metal oxide is 1.02 to 1.05.
[0010] The all-solid-state battery positive electrode active material may have a half-maximum width (FWHM) (110) of the (110) plane diffraction peak of 0.15 to 0.25 during X-ray diffraction spectrum analysis.
[0011] The all-solid-state battery cathode active material may have an average crystallite size of 100 to 120 nm.
[0012] The all-solid-state battery positive electrode active material may have a specific surface area of 0.4 to 0.7 m 2 / g.
[0013] The lithium transition metal oxide may be represented by Chemical Formula 1 below.
[0014] [Chemical Formula 1]
[0015] Li a [Ni x1 Co y1 M z1 ]O2
[0016] In the above chemical formula 1, 1.01≤a≤1.05, 0.60≤x1<1, 0≤y1≤0.2, 0 <z1≤0.2,x1+y1+z1=1,M是Mn、Al、Mg、Ti、Nb、W、Sc、Zr、Si、V、Fe、Y、Mo或它们的组合。
[0017] The lithium ion conductive oxide may be represented by the following Chemical Formula 2.
[0018] [Chemical Formula 2]
[0019] Li x2 A y2 O z2
[0020] In the above chemical formula 2, 0≤x2≤3, 0 <y2≤2,0<z2≤4,A是Zr、Nb、Ti或它们的组合。
[0021] The lithium ion conductive oxide may be Li2ZrO3, ZrO2, LiNbO3, Nb2O3, Li2TiO3, TiO2, or a combination thereof.
[0022] Based on the total weight of the positive electrode active material, the content of the coating may be 0.5 to 1.5% by weight.
[0023] Another embodiment of the present invention provides a method for preparing a positive electrode active material for an all-solid-state battery, which includes: preparing a transition metal hydroxide containing nickel and having an average particle size (D50) of 4 to 6 μm; forming a mixture containing the transition metal hydroxide and a lithium raw material such that the molar ratio of lithium (Li) to the transition metal (Me) (Li / Me) is 1.02 to 1.05; calcining the mixture to form a lithium transition metal oxide; and forming a coating containing a lithium ion conductive oxide on the surface of the lithium transition metal oxide.
[0024] In the step of forming the lithium transition metal oxide, the calcination may be carried out at a temperature of 720 to 760 °C.
[0025] In the step of preparing the transition metal hydroxide, the transition metal hydroxide may have a structure including sheet-like primary particles.
[0026] Another embodiment of the present invention provides a positive electrode including the aforementioned positive electrode active material for an all-solid-state battery.
[0027] Another embodiment of the present invention provides an all-solid-state battery including a positive electrode; a negative electrode; and a solid electrolyte layer disposed between the positive electrode and the negative electrode, wherein the positive electrode includes the aforementioned positive electrode active material for an all-solid-state battery.
[0028] Advantageous Effects
[0029] The positive electrode active material for an all-solid-state battery according to an embodiment of the present invention includes a coating containing a lithium ion conductive oxide to inhibit the formation of an impedance layer. By adjusting the average particle size, the ratio of the diffraction peak intensity of the (104) plane to the diffraction peak intensity of the (003) plane I(003) / I(104) during X-ray diffraction spectrum analysis, etc., the output characteristics can be maximized. Description of the Drawings
[0030] Figure 1 are SEM images of the precursors used in Example 1 and Comparative Example 1 and the positive electrode active materials prepared therefrom. Detailed Description
[0031] The terms first, second, third, etc. are used to describe various parts, components, regions, layers, and / or segments, but these parts, components, regions, layers, and / or segments should not be limited by these terms. These terms are only used to distinguish one part, component, region, layer, and / or segment from another part, component, region, layer, and / or segment. Therefore, without departing from the scope of the present invention, the first part, component, region, layer, and / or segment described below can also be described as the second part, component, region, layer, and / or segment.
[0032] The terms used herein are only for describing specific embodiments and are not intended to limit the present invention. Unless otherwise clearly indicated to the contrary in the context, the singular forms used are also intended to include the plural forms. It should also be understood that the term "comprising" used in the specification can specifically refer to a certain characteristic, field, integer, step, action, element, and / or component, but does not exclude the existence or addition of other characteristics, fields, integers, steps, actions, elements, and / or components.
[0033] If a part is described as being above another part, there may be other parts directly above the other part or there may be other parts therebetween. When a part is described as being directly above another part, there will be no other parts therebetween.
[0034] Unless otherwise defined, the meanings of all terms (including technical terms and scientific terms) used herein are the same as those commonly understood by those of ordinary skill in the art to which the present invention pertains. For terms defined in a dictionary, they should be interpreted as having a meaning consistent with the relevant technical literature and the content disclosed herein, and should not be interpreted in an idealized or overly formal sense.
[0035] In addition, unless otherwise specifically described, % represents % by weight, and 1 ppm represents 0.0001% by weight.
[0036] In this specification, the "combinations thereof" described in the Markush-type expressions refer to one or more mixtures or combinations selected from the group consisting of the constituent elements recited in the Markush-type expressions, meaning including one or more selected from the group consisting of the above-mentioned constituent elements.
[0037] Hereinafter, embodiments of the present invention will be described in detail so that those of ordinary skill in the art to which the present invention pertains can easily implement the present invention. However, the present invention can be implemented in various different ways and is not limited to the embodiments described herein.
[0038] 1. Cathode active material for all-solid-state battery
[0039] One embodiment of the present invention provides a positive electrode active material for an all-solid-state battery, which comprises: a core containing a layered lithium transition metal oxide; and a coating disposed on the core and containing a lithium ion conductive oxide, wherein the ratio I(003) / I(104) of the diffraction peak intensity of the (104) plane to the diffraction peak intensity of the (003) plane in X-ray diffraction spectroscopy is 1.20 to 1.40, and the molar ratio of lithium / transition metal (Li / Me) of the lithium transition metal oxide is 1.02 to 1.05.
[0040] The positive electrode active material according to one embodiment of the present invention can be used in an all-solid-state battery. More specifically, it can be a positive electrode active material in a composite positive electrode material for use with a sulfide-based solid electrolyte.
[0041] The positive electrode active material for an all-solid-state battery according to one embodiment of the present invention can include a core and a coating disposed on the core.
[0042] At this time, the positive electrode active material for an all-solid-state battery according to one embodiment of the present invention can be secondary particles formed by aggregation of a plurality of primary particles.
[0043] In this specification, a "primary particle" refers to the smallest particle unit that is distinguished as a single piece when observing the cross-section of the positive electrode active material through a scanning electron microscope (SEM), and can be composed of a single crystal grain or a plurality of crystal grains.
[0044] On the other hand, the coating contains a lithium ion conductive oxide. Since the coating is included as described above, it is possible to prevent the formation of a high-impedance layer caused by a side reaction between the layered lithium transition metal oxide and the sulfide-based solid electrolyte, thereby improving the battery capacity and life characteristics.
[0045] The lithium ion conductive oxide can be an oxide containing zirconium (Zr), niobium (Nb), titanium (Ti), or a combination thereof.
[0046] More specifically, the lithium ion conductive oxide can be represented by the following Chemical Formula 2.
[0047] [Chemical Formula 2]
[0048] Li x2 A y2 O z2
[0049] In the above Chemical Formula 2, 0 ≤ x2 ≤ 3, 0 < y2 ≤ 2, 0 < z2 ≤ 4, and A is Zr, Nb, Ti, or a combination thereof.
[0050] For example, the lithium ion conductive oxide may be Li2ZrO3, ZrO2, LiNbO3, Nb2O3, Li2TiO3, TiO2, or a combination thereof, but is not limited thereto.
[0051] However, since the positive electrode active material is coated with the lithium ion conductive oxide, the initial capacity and efficiency of the battery and the charge-discharge life characteristics are greatly improved, but there is a problem that the discharge capacity decreases significantly at high c-rate.
[0052] To improve this, the positive electrode active material of the all-solid-state battery according to an embodiment of the present invention further adjusts the average particle size (D50), the ratio I(003) / I(104) of the diffraction peak intensity of the (104) plane to the diffraction peak intensity of the (003) plane during X-ray diffraction spectrum analysis, and the molar ratio of lithium / transition metal (Li / Me) of the lithium transition metal oxide.
[0053] In addition, the ratio I(003) / I(104) of the diffraction peak intensity of the (104) plane to the diffraction peak intensity of the (003) plane during X-ray diffraction spectrum analysis of the positive electrode active material according to an embodiment of the present invention is 1.20 to 1.40, and more specifically may be 1.23 to 1.39.
[0054] Generally, the peak intensity value refers to the integrated area value obtained by integrating the height value or the area of the peak. In this embodiment, the peak intensity value refers to the area value of the peak.
[0055] The positive electrode active material of the all-solid-state battery may have a full width at half maximum FWHM(110) of the diffraction peak of the (110) plane of 0.15 to 0.25 during X-ray diffraction spectrum analysis.
[0056] The positive electrode active material of the all-solid-state battery may have an average crystallite size of 100 to 120 nm. In this specification, "crystallite" refers to a single crystal grain unit having a regular atomic arrangement. For the size of the crystallite, for example, a high-resolution transmission electron microscope (HR-TEM) TITAN G2 can be used to measure by magnifying the sample surface 800,000 to 2,000,000 times, and the average crystallite size can be obtained by calculating the arithmetic average of the measured crystallite sizes.
[0057] When the peak intensity ratio I(003) / I(104) of the positive electrode active material, the full width at half maximum FWHM(110) of the diffraction peak of the (110) plane, and the average crystallite size satisfy the above ranges, the contact interface between the active material and the solid electrolyte is maximized, the lithium migration path inside the secondary particles is minimized, the structural stability of the active material is improved, and the initial capacity, output (rate), and life characteristics of the battery can be further improved.
[0058] In particular, the molar ratio of lithium / transition metal (Li / Me) of the lithium transition metal oxide contained in the positive electrode active material according to an embodiment of the present invention is 1.02 to 1.05, and more specifically, it may be 1.03 to 1.04.
[0059] When the molar ratio of Li / Me of the lithium transition metal oxide satisfies the above range, the peak intensity ratio I(003) / I(104), the full width at half maximum FWHM(110) of the diffraction peak of the (110) plane, and the average crystallite size of the aforementioned active material easily reach the target range, which is of great significance for improving the capacity, output (rate), and life characteristics of the battery.
[0060] In addition, the average particle size (D50) of the positive electrode active material according to an embodiment of the present invention is 3 to 6 μm, and more specifically, it may be 3.5 to 5.5 μm.
[0061] In this specification, the average particle size (D50) can be defined as the particle size corresponding to 50% of the volume cumulative amount on the particle size distribution curve of the particles. For the average particle size (D50), for example, the laser diffraction method can be used for measurement. The light diffraction method can generally measure particle sizes from the submicron region to about a few millimeters, and results with high reproducibility and high resolution can be obtained.
[0062] When the average particle size (D50) of the active material satisfies the above range, the contact interface between the active material and the solid electrolyte is maximized, the lithium migration path inside the secondary particles is minimized, and the capacity and output (rate) characteristics of the battery can be improved.
[0063] In addition, the specific surface area of the positive electrode active material of the all-solid-state battery may be 0.4 to 0.7 m 2 / g, and more specifically, it may be 0.45 to 0.65 m 2 / g.
[0064] In this specification, for the specific surface area of the active material, the BET method (Surface area and Porosity analyzer) (Micromeritics, ASAP2020) can be used to measure the active material powder.
[0065] When the specific surface area of the active material satisfies the above range, the above-mentioned battery performance improvement effect can be better achieved, and the life characteristics can be improved.
[0066] More specifically, the lithium transition metal oxide can be represented by the following Chemical Formula 1.
[0067] [Chemical Formula 1]
[0068] Li a [Ni x1 Co y1 M z1 O2
[0069] In the above Chemical Formula 1, 1.01 ≤ a ≤ 1.05, 0.60 ≤ x1 < 1, 0 ≤ y1 ≤ 0.2, 0 < z1 ≤ 0.2, x1 + y1 + z1 = 1, and M is Mn, Al, Mg, Ti, Nb, W, Sc, Zr, Si, V, Fe, Y, Mo, or a combination thereof.
[0070] In the lithium transition metal oxide of the above Chemical Formula 1, the lithium content can correspond to a, that is, 1.01 ≤ a ≤ 1.05. When a satisfies the above range, it is easy to achieve the peak intensity ratio I(003) / I(004), the full width at half maximum FWHM(110) of the (110) plane diffraction peak, and the average grain size of the active material as described above.
[0071] In the lithium transition metal oxide of the above Chemical Formula 1, the nickel content can correspond to x1, that is, 0.60 ≤ x < 1. When x is large enough to be above 0.60, the nickel content contributing to charge and discharge can be ensured, thereby achieving a high capacity of the battery. More specifically, it can be 0.80 ≤ x < 1.
[0072] In the lithium transition metal oxide of the above Chemical Formula 1, the cobalt content can correspond to y1, that is, 0 ≤ y1 ≤ 0.2. If the cobalt content is too low, there is a problem that it is difficult to simultaneously achieve sufficient rate characteristics and a high powder density of the active material. If the cobalt content is too high, there are problems of an overall increase in the cost of raw materials and a decrease in the reversible capacity.
[0073] In the lithium transition metal oxide of the above Chemical Formula 1, M is an element other than lithium, nickel, and cobalt, and M is Mn, Al, Mg, Ti, Nb, W, Sc, Zr, Si, V, Fe, Y, Mo, or a combination thereof. The content of these Ms can correspond to z1, that is, 0 < z1 ≤ 0.2.
[0074] Based on the total weight of the positive electrode active material, the content of the coating can be 0.5 to 1.5% by weight. If the content of the coating is too small, the above-mentioned battery performance improvement effect may be very small, and if the content of the coating is too large, the content of the lithium transition metal oxide becomes small, which may lead to a decrease in the capacity of the battery.
[0075] 2. Preparation method of positive electrode active material for all-solid-state battery
[0076] Another embodiment of the present invention provides a method for preparing a positive electrode active material for an all-solid-state battery, which includes the following steps: preparing a transition metal hydroxide containing nickel and having an average particle size (D50) of 4 to 6 μm; forming a mixture containing the transition metal hydroxide and a lithium raw material such that the molar ratio of lithium (Li) to the transition metal (Me) (Li / Me) is 1.01 to 1.05; calcining the mixture to form a lithium transition metal oxide; and forming a coating containing a lithium ion conductive oxide on the surface of the lithium transition metal oxide.
[0077] Hereinafter, the method for preparing a positive electrode active material for an all-solid-state battery according to another embodiment of the present invention will be described according to each step.
[0078] First, prepare a transition metal hydroxide containing nickel and having an average particle size (D50) of 4 to 6 μm.
[0079] The transition metal hydroxide is a positive electrode active material precursor.
[0080] At this time, the positive electrode active material precursor can be secondary particles formed by aggregation of primary particles.
[0081] In particular, the average particle size (D50) of the transition metal hydroxide is 4 to 6 μm. Therefore, the average particle size (D50) of the positive electrode active material easily reaches the target range.
[0082] In addition, the transition metal hydroxide can have a thin plate-like shape. Therefore, it has the advantage that the migration of lithium ions in the vertical direction on the precursor sheet is easier.
[0083] For the transition metal hydroxide, for example, an ammonia solution and a caustic soda solution can be added to a transition metal-containing solution comprising a nickel raw material substance, a cobalt raw material substance, a manganese raw material substance, and a doping raw material substance containing Al, Mg, Ti, Nb, W, Sc, Zr, Si, V, Fe, Y, Mo, or a combination thereof to carry out a coprecipitation reaction, thereby preparing the transition metal hydroxide.
[0084] For the nickel raw material substance, if it is a substance used in the relevant industry for preparing the precursor of the positive electrode active material, there is no particular limitation. For example, the nickel raw material substance may be nickel sulfate, acetate, nitrate, halide, sulfide, hydroxide, oxide, or oxyhydroxide, etc. Specifically, it may be NiSO4, NiSO4·6H2O, Ni(OH)2, NiO, NiOOH, NiCO3·2Ni(OH)2·4H2O, NiC2O2·2H2O, Ni(NO3)2·6H2O, nickel fatty acid salt, nickel halide, or a combination thereof, but not limited thereto.
[0085] For the cobalt raw material substance, if it is a substance used in the relevant industry for preparing the precursor of the positive electrode active material, there is no particular limitation. For example, the cobalt raw material substance may be cobalt sulfate, acetate, nitrate, halide, sulfide, hydroxide, oxide, or oxyhydroxide, etc. Specifically, it may be CoSO4, CoSO4·7H2O, Co(OH)2, CoOOH, Co(OCOCH3)2·4H2O, Co(NO3)2·6H2O, or a combination thereof, but not limited thereto.
[0086] For the manganese raw material substance, if it is a substance used in the relevant industry for preparing the precursor of the positive electrode active material, there is no particular limitation. For example, the manganese raw material substance may be manganese sulfate, acetate, nitrate, halide, sulfide, hydroxide, oxide, oxyhydroxide, or a combination thereof. Specifically, it may be manganese salts such as MnSO4, MnCO3, Mn(NO3)2, manganese acetate, manganese dicarboxylate salts, manganese citrate, and manganese fatty acid salts, manganese oxides such as Mn2O3, MnO2, and Mn3O4, manganese oxyhydroxide, manganese chloride, or a combination thereof, but not limited thereto.
[0087] For the transition metal-containing solution, the transition metal-containing solution can be prepared by adding the raw material substances to a solvent. The solvent may specifically be water or a mixed solvent of an organic solvent (such as alcohol, etc.) that can be uniformly mixed with water, or the transition metal-containing solution can be prepared by mixing aqueous solutions containing each raw material substance.
[0088] The ammonia solution, as a complexing agent, may contain, for example, NH3, NH4OH, (NH4)2SO4, NH4NO3, NH4Cl, CH3COONH4, NH4CO3, or a combination thereof, but is not limited thereto. On the other hand, the ammonia solution may also be in the form of an aqueous solution, in which case the solvent may be water or a mixture of water and an organic solvent (specifically, alcohols, etc.) that can be uniformly mixed with water.
[0089] The caustic soda solution, as a precipitating agent or pH regulator, may contain basic compounds such as hydroxides of alkali metals or alkaline earth metals, their hydrates, or combinations thereof, such as NaOH, KOH, or Ca(OH)2. The caustic soda solution may also be in the form of an aqueous solution, in which case the solvent may be water or a mixture of water and an organic solvent (specifically, alcohols, etc.) that can be uniformly mixed with water.
[0090] The coprecipitation reaction may be carried out under an inert atmosphere such as nitrogen or argon.
[0091] Next, a mixture containing a transition metal hydroxide and a lithium raw material is formed such that the molar ratio of lithium (Li) to the transition metal (Me) (Li / Me) is 1.02 to 1.05.
[0092] The lithium raw material may be a lithium-containing sulfate, nitrate, acetate, carbonate, oxalate, citrate, halide, hydroxide, or hydroxyoxide, etc., and is not particularly limited as long as it is soluble in water. Specifically, the lithium raw material may be Li2CO3, LiNO3, LiNO2, LiOH, LiOH·H2O, LiH, LiF, LiCl, LiBr, LiI, CH3COOLi, Li2O, Li2SO4, CH3COOLi, Li3C6H5O7, or a combination thereof, but is not limited thereto.
[0093] The mixture may further contain a doping raw material containing Al, Mg, Ti, Nb, W, Sc, Zr, Si, V, Fe, Y, Mo, or a combination thereof.
[0094] In particular, at this time, the mixture is adjusted so that the molar ratio of lithium (Li) to the transition metal (Me) (Li / Me) is 1.02 to 1.05, and more specifically, it can be adjusted to 1.03 to 1.04. Therefore, the Li / Me ratio in the lithium transition metal oxide of the active material is adjusted to the same ratio, and the advantages brought about thereby are as described above, so the description is omitted here.
[0095] Next, the mixture is calcined to form a lithium transition metal oxide.
[0096] At this time, the calcination can be carried out at a temperature of 720 to 760 °C. When the calcination temperature satisfies the above range, it has the advantage of being able to ensure the optimal grain size.
[0097] The calcination can be carried out for 5 to 20 hours, more specifically, it can be carried out for 5 to 15 hours or 8 to 12 hours.
[0098] The calcination can be carried out in an oxygen atmosphere.
[0099] Next, a coating containing a lithium ion conductive oxide is formed on the surface of the lithium transition metal oxide.
[0100] The lithium ion conductive oxide is as described above, so a detailed description is omitted.
[0101] On the other hand, the coating formation method is not particularly limited. For example, a coating solution containing the coating raw material substance can be sprayed on the surface of the lithium transition metal oxide, and then formed by heat treatment and drying, but it is not limited thereto, and any method used in the relevant industry can be adopted without limitation.
[0102] 3. All-solid-state battery
[0103] Another embodiment of the present invention provides a positive electrode comprising the aforementioned all-solid-state battery positive electrode active material.
[0104] More specifically, the positive electrode may comprise a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector. The positive electrode active material layer may comprise the aforementioned all-solid-state battery positive electrode active material, a sulfide-based solid electrolyte, and a conductive material. In addition, the positive electrode active material layer may further comprise a binder.
[0105] For the sulfide-based solid electrolyte, for example, it may be a sulfide-based solid electrolyte having a thiogermanate crystal structure.
[0106] For the sulfide-based solid electrolyte having a thiogermanate crystal structure, specifically, it may be a compound represented by Li 7- x PS 6-x D x (0 ≤ x ≤ 2, D is F, Cl, Br, I, or a combination thereof).
[0107] For example, the sulfide-based solid electrolyte having a thiogermanate crystal structure may be Li6PS5Cl, Li6PS5Br, Li6PS5I, or a combination thereof, but it is not limited thereto.
[0108] For the sulfide-based solid electrolyte having an argyrodite crystal structure, at least a part of the crystal structure may be doped with a doping element. Thereby, the air stability can be improved.
[0109] For the conductive material, for example, it may be graphite, carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, Tokai black, Denka black, Super P, carbon nanotubes, carbon nanofibers, graphene, fullerenes, or a combination thereof, but not limited thereto.
[0110] For the binder, for example, it may be polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polymethacrylate, ethylene-propylene-diene monomer rubber (EPDM rubber), sulfonated-EPDM, styrene-butadiene rubber (SBR), butadiene rubber (BR), nitrile rubber (NBR), styrene-butadiene-styrene block polymer (SBS), styrene-ethylene-butadiene block polymer (SEB), styrene-(styrene-butadiene)-styrene block polymer, natural rubber (NR), isoprene rubber (IR), fluororubber, or a combination thereof, but not limited thereto.
[0111] For the positive electrode active material layer, in addition to the aforementioned positive electrode active material, solid electrolyte, binder, and conductive material, for example, it may further contain additives such as filler, coating agent, dispersant, and ion conduction promoter.
[0112] Another embodiment of the present invention provides an all-solid-state battery, which includes a positive electrode; a negative electrode; and a solid electrolyte layer disposed between the positive electrode and the negative electrode, and the positive electrode includes the aforementioned all-solid-state battery positive electrode active material.
[0113] The description of the positive electrode is as described above, so the repetitive description is omitted.
[0114] The solid electrolyte layer may contain a sulfide-based solid electrolyte.
[0115] For the sulfide-based solid electrolyte, for example, it may be a sulfide-based solid electrolyte having an argyrodite crystal structure.
[0116] For the sulfide-based solid electrolyte having an argyrodite crystal structure, specifically, it may be composed of Li 7-x PS 6- x D xA compound represented by (0 ≤ x ≤ 2, where D is F, Cl, Br, I, or a combination thereof).
[0117] For example, the sulfide-based solid electrolyte having a thiogermanate crystal structure may be Li6PS5Cl, Li6PS5Br, Li6PS5I, or a combination thereof, but is not limited thereto.
[0118] For the sulfide-based solid electrolyte having a thiogermanate crystal structure, at least a part of its crystal structure may be doped with a doping element. Thereby, the air stability can be improved.
[0119] The solid electrolyte contained in the positive electrode active material layer and the solid electrolyte contained in the solid electrolyte layer may be the same or different.
[0120] The solid electrolyte layer may further contain a binder. Examples of the binder contained in the solid electrolyte layer may be polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polymethacrylate, ethylene-propylene-diene monomer rubber (EPDM rubber), sulfonated-EPDM, styrene-butadiene rubber (SBR), butadiene rubber (BR), nitrile rubber (NBR), styrene-butadiene-styrene block polymer (SBS), styrene-ethylene-butadiene block polymer (SEB), styrene-(styrene-butadiene)-styrene block polymer, natural rubber (NR), isoprene rubber (IR), fluororubber, or a combination thereof, but is not limited thereto.
[0121] At this time, the binder contained in the solid electrolyte layer and the binder contained in the positive electrode active material layer or the negative electrode active material layer may be the same or different.
[0122] The negative electrode may include a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector, and the negative electrode active material layer may contain a negative electrode active material.
[0123] The negative electrode active material contains a substance capable of reversibly inserting and extracting lithium ions, lithium metal, an alloy of lithium metal, a substance capable of doping and dedoping lithium, or a transition metal oxide.
[0124] As the substance capable of reversibly inserting / extracting lithium ions, any carbonaceous negative electrode active material generally used in lithium ion secondary batteries as a carbon material can be used. As typical examples thereof, crystalline carbon, amorphous carbon, or a combination thereof can be used. As examples of the crystalline carbon, natural graphite or artificial graphite such as amorphous, plate-like, flaky, spherical, or fibrous graphite can be cited. As examples of the amorphous carbon, soft carbon (low-temperature calcined carbon), hard carbon, mesophase pitch carbide, calcined coke, etc. can be cited.
[0125] As the alloy of the lithium metal, an alloy of lithium and a metal selected from Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn can be used.
[0126] As the substance capable of doping and dedoping lithium, Si, SiOx (0 < x < 2), Si-Y alloy (wherein Y is an element selected from alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements, transition metals, rare earth elements, and combinations thereof, but not Si), Sn, SnO2, Sn-Y (wherein Y is an element selected from alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements, transition metals, rare earth elements, and combinations thereof, but not Sn), etc. can be cited. At least one of them can also be used in combination with SiO2. The element Y can be selected from Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Ti, Ge, P, As, Sb, Bi, S, Se, Te, Po, and combinations thereof.
[0127] As the transition metal oxide, vanadium oxide, lithium vanadium oxide, etc. can be cited.
[0128] The negative electrode active material layer also contains a binder, and may also selectively further contain a conductive material.
[0129] The binder serves to bond the negative electrode active material particles well to each other and to bond the negative electrode active material well to the current collector. Typical examples thereof include polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, a polymer containing ethylene oxide, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, nylon, etc., but are not limited thereto.
[0130] The conductive material is used to impart conductivity to the electrode, and any conductive material can be used as long as it does not cause chemical changes in the formed battery. Examples thereof may include carbon materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, etc.; metal materials such as metal powders or metal fibers of copper, nickel, aluminum, silver, etc.; conductive polymer materials such as polyphenylene derivatives, etc.; or mixtures thereof.
[0131] As the current collector, a material selected from copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer material coated with a conductive metal, and combinations thereof can be used.
[0132] Hereinafter, embodiments of the present invention will be described in further detail through examples. However, the following examples are a preferred embodiment of the present invention, and the present invention is not limited to the following examples.
[0133] Example 1
[0134] (1) Preparation of the positive electrode active material
[0135] (Preparation of transition metal hydroxide) Prepare Ni(OH)₂ transition metal hydroxide having an average particle diameter (D50) of 5 μm and a thin plate-like structure. 0.83 Co 0.12 Mn 0.05 (OH)₂ transition metal hydroxide.
[0136] (Formation of lithium transition metal oxide) Mix the lithium (Li) and transition metal (Me) in LiOH in the transition metal hydroxide to have a molar ratio (Li / Me) of 1.03, and calcine in an oxygen atmosphere at a temperature of 730 °C for 10 hours to form LiNiCoMnO₂ lithium transition metal oxide. 1.03 Ni 0.83 Co 0.12 Mn 0.05 O₂ lithium transition metal oxide.
[0137] (Formation of coating) Next, dissolve lithium metal in absolute ethanol to prepare a lithium ethoxide solution. Mix a 70 wt% propanol solution of zirconium(IV) tetrapropanolate into the prepared solution, and then stir for more than 10 minutes to prepare a coating solution. Put the prepared coating solution into a fluidized bed coating device, load the prepared lithium transition metal oxide, and then perform wet coating with a solution concentration of 0.03 mol, a solution supply rate of 6 cc / min, and a coating solution spraying time of 60 minutes. Then, perform heat treatment at 300 °C in an oxygen atmosphere for 2 hours to prepare a positive electrode active material having a Li₂ZrO₃ coating formed on the surface of the lithium transition metal oxide.
[0138] (2) Preparation of all-solid-state battery
[0139] 72 wt% of the prepared cathode active material was mixed with 25 wt% of argyrodite solid electrolyte (Li6PS5Cl) and 3 wt% of Super C65 as a conductive material to prepare a mixed powder.
[0140] First, 100 mg of argyrodite solid electrolyte (Li6PS5Cl) with a diaphragm function was loaded into a jig for evaluating all-solid-state batteries, pressed at a pressure of 300 Mpa or more to a thickness of about 100 μm, and then the mixed powder was loaded on one side so that the amount of the cathode active material reached 14.4 mg, followed by secondary pressing to fabricate the cathode part.
[0141] Then, Li-In alloy was loaded on the other side and an appropriate pressure was applied to fabricate a battery for evaluating all-solid-state batteries.
[0142] Example 2
[0143] Except that the calcination temperature was set at 740 °C when forming the lithium transition metal oxide, the cathode active material and the all-solid-state battery were prepared in the same manner as in Example 1.
[0144] Comparative Example 1
[0145] Except that the molar ratio of Li / Me was 1.01 when forming the lithium transition metal oxide, the cathode active material and the all-solid-state battery were prepared in the same manner as in Example 1.
[0146] Comparative Example 2
[0147] Except that the molar ratio of Li / Me was 1.07 when forming the lithium transition metal oxide, the cathode active material and the all-solid-state battery were prepared in the same manner as in Example 1.
[0148] Comparative Example 3
[0149] Except that a transition metal hydroxide with an average particle size (D50) of 6.2 μm was prepared, the cathode active material and the all-solid-state battery were prepared in the same manner as in Example 1.
[0150] Comparative Example 4
[0151] Except that a transition metal hydroxide with an average particle size (D50) of 6.5 μm was prepared, the cathode active material and the all-solid-state battery were prepared in the same manner as in Example 1.
[0152] Experimental Example 1: SEM Image Analysis of Precursors and Active Materials
[0153] SEM (scanning electron microscope) images of the transition metal hydroxides (precursors) used in Example 1 and Comparative Example 1 and the positive electrode active materials prepared therefrom are shown in Figure 1 Figures 4 to 6.
[0154] Specifically, Figure 1 Figures 2 and 4 are SEM images of the precursors used in Example 1 and Comparative Example 1, respectively.
[0155] Figures 2 to 3 are SEM images of the positive electrode active materials prepared according to Example 1.
[0156] Figures 5 to 6 are SEM images of the positive electrode active materials prepared according to Comparative Example 1.
[0157] Experimental Example 2: Physical Property Evaluation of Positive Electrode Active Material
[0158] The physical properties of the positive electrode active materials prepared according to the examples and comparative examples were evaluated and are shown in Table 1 below. The specific experimental methods are as follows.
[0159]
Table 1
[0160]
[0161]
[0162] Experimental Example 3: Electrochemical Property Evaluation of Lithium Secondary Battery
[0163] The electrochemical properties of the lithium secondary batteries prepared according to the examples and comparative examples were evaluated and are shown in Table 2 below. The specific experimental methods are as follows.
[0164] (1) Evaluation of 0.1C initial charge and discharge capacity, initial efficiency
[0165] The fabricated all-solid-state battery cell for evaluation was installed on a charger / discharger, and the charge and discharge characteristics were evaluated at 30 degrees. For the charge and discharge method, the first charge was carried out by the constant current-voltage method at a current density of 0.1C. The terminal charge voltage was set to 3.7V, and the charge termination current was set to a current of 0.02C. During discharge, the constant current method of 0.1C was used for discharge, and the charge termination voltage was set to 1.9V. The charge capacity, discharge capacity, and initial efficiency at this time were measured.
[0166] (2) Evaluation of 2.0C high-rate discharge capacity
[0167] The 2.0C high-rate discharge capacity was evaluated.
[0168] (3) Evaluation of life characteristics (30 cycles, 0.5C)
[0169] The life characteristics are evaluated by measuring the discharge capacity ratio after 30 cycles relative to the initial discharge capacity.
[0170]
Table 2
[0171]
[0172] For Examples 1 and 2 in which the Li / Me ratio, the I(003) / I(104) peak intensity ratio, FWHM(110), the average grain size, and the specific surface area are all appropriately adjusted, it can be confirmed that the initial capacity, efficiency, high-rate characteristics, and life characteristics of the battery are all very excellent. On the other hand, for Comparative Examples 1 to 4, since the Li / Me molar ratio or the average particle size of the transition metal hydroxide is not appropriately adjusted when forming the transition metal oxide, the appropriate physical property values of the active material are not obtained, and it can be confirmed that the battery performance is poor.
[0173] Although the preferred embodiments of the present invention have been described above, the present invention is not limited thereto, and various modifications can be made within the scope of the claims, the specification, and the drawings, and these modifications also fall within the scope of the present invention.
[0174] Therefore, the substantial scope of the present invention is defined by the claims and their equivalents.
Claims
1. A positive electrode active material for an all-solid-state battery, comprising: a core comprising a layered lithium transition metal oxide; and a coating disposed on the core and containing a lithium ion conductive oxide, the ratio I(003) / I(104) of the diffraction peak intensity of the (104) plane to the diffraction peak intensity of the (003) plane during X-ray diffraction spectroscopy analysis is 1.20 to 1.40, the molar ratio of lithium / transition metal (Li / Me) of the lithium transition metal oxide is 1.02 to 1.
05.
2. The positive electrode active material for an all-solid-state battery according to claim 1, wherein, the full width at half maximum FWHM(110) of the diffraction peak of the (110) plane during X-ray diffraction spectroscopy analysis is 0.15 to 0.
25.
3. The positive electrode active material for an all-solid-state battery according to claim 1, wherein, the average grain size is 100 to 120 nm.
4. The positive electrode active material for an all-solid-state battery according to claim 1, wherein, The specific surface area is 0.4 to 0.7 m 2 / g.
5. The positive electrode active material for an all-solid-state battery according to claim 1, wherein, the lithium transition metal oxide is represented by the following Chemical Formula 1: [Chemical Formula 1] Li a [Ni x1 Co y1 M z1 O2 In the above Chemical Formula 1, 1.02 ≤ a ≤ 1.05, 0.60 ≤ x1 < 1, 0 ≤ y1 ≤ 0.2, 0 < z1 ≤ 0.2, x1 + y1 + z1 = 1, and M is Mn, Al, Mg, Ti, Nb, W, Sc, Zr, Si, V, Fe, Y, Mo, or a combination thereof.
6. The positive electrode active material for an all-solid-state battery according to claim 1, wherein, the lithium ion conductive oxide is represented by the following Chemical Formula 2: [Chemical Formula 2] Li x2 A y2 O z2 In the above Chemical Formula 2, 0 ≤ x2 ≤ 3, 0 < y2 ≤ 2, 0 < z2 ≤ 4, and A is Zr, Nb, Ti, or a combination thereof.
7. The positive electrode active material for an all-solid-state battery according to claim 1, wherein, the lithium ion conductive oxide is Li2ZrO3, ZrO2, LiNbO3, Nb2O3, Li2TiO3, TiO2, or a combination thereof.
8. The positive electrode active material for an all-solid-state battery according to claim 1, wherein, based on the total weight of the positive electrode active material, the content of the coating is 0.5 to 1.5% by weight.
9. A method for preparing a positive electrode active material for an all-solid-state battery, comprising the following steps: preparing a transition metal hydroxide containing nickel and having an average particle size (D50) of 4 to 6 μm; forming a mixture comprising the transition metal hydroxide and a lithium raw material such that the molar ratio of lithium (Li) to the transition metal (Me) (Li / Me) is 1.02 to 1.05; calcining the mixture to form a lithium transition metal oxide; and forming a coating containing a lithium ion conductive oxide on the surface of the lithium transition metal oxide.
10. The method for preparing a positive electrode active material for an all-solid-state battery according to claim 9, wherein, in the step of forming the lithium transition metal oxide, the calcination is carried out at a temperature of 720 to 760 °C.
11. The method for preparing a positive electrode active material for an all-solid-state battery according to claim 9, wherein, In the step of preparing the transition metal hydroxide, the transition metal hydroxide has a structure including sheet-like primary particles.
12. A positive electrode comprising the all-solid-state battery positive electrode active material according to any one of claims 1 to 8.
13. An all-solid-state battery comprising a positive electrode; a negative electrode; and a solid electrolyte layer disposed between the positive electrode and the negative electrode, wherein the positive electrode comprises the all-solid-state battery positive electrode active material according to any one of claims 1 to 8.